Wolfen [videorecording (DVD)] - Finney, Albert, 1936-2019-; Hines, Gregory; Venora, Diane; Olmos, Edward James; Strieber, Whitley (Warner Home Video, 2002)
Scary tale of a series of grisly murders in Manhattan, and the rumpled cop who finally discovers who (or what) is responsible.